Relationships among egfr, vitamin d metabolites and pth 1-84 in ckd. - K. Phelps; R. Mathew; K. Stote; L. Hewson; D. Hallenbeck (Kidney Research and Clinical Practice, 2012)
Vitamin D undergoes 25-hydroxylation in the liver (25D) and 1-alpha hydroxylation in the kidney (1,25D). Both [25D] and [1,25D] fell with GFR in surveys of patients with CKD. Because 1,25D suppresses transcription of the PTH gene, low [1,25D] is thought to be a cause of high [PTH] in CKD. To examine relationships among eGFR, [PTH] 1–84 (Scantibodies), [25D], and [1,25D], we studied 8 normal subjects with eGFR 73–103 and 29 patients with eGFR 14–49 ml/min/1.73 m2. Most patients had been taking supplemental vitamin D. Means (SEM) were compared by two-tailed t-test, and regressions were examined as indicated below. Results are summarized in the tables. Variable CKD (n=29) Nl (n=8) p eGFR (ml/min/1.73 m2) 30.0 (1.7) 88.6 (4.0) < 0.001 [PTH] pg/ml 80.6 (8.6) 30.1 (3.7) 0.005 [25D] ng/ml 35.2 (2.5) 39.7 (3.4) 0.4 [1,25D] pg/ml 42.5 (3.6) 55.1 (4.8) 0.1